Mindfulness for human-centred digital learning - Palalas, Agnieszka (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Drawing from a decade of informed exploration, educational research and personal practice, this reflective article discusses the construct of mindfulness and its application in digital learning, including language learning. Latest discoveries in neuroscience and scientific research in mindfulness, have bridged the science and practice of mindfulness providing evidence on its positive effects on human-centred teaching and learning. Regular mindfulness practice can alter the function and structure of the brain and help learners train their mind to, among other skills, pay attention in a purposeful way and not get distracted by the abundance of external and internal stimuli. It can promote learners’ awareness, self-regulation, and other metacognitive skills so they become more resilient and ready to face the challenges of the increasinglyoverwhelming digital world.